DESAIN SANITARY LANDFILL PADA TOPOGRAFI EXTREM DI DESA DONOWARIH KECAMATAN KARANGPLOSO KABUPATEN MALANG - Septiropa, Zamzami (Jurnal Gamma, 2010)
Village Donowarih Karangploso District of Malang Regency is one of the areas that havetrouble and waste management in the central (dumped in landfills / TPA) where the existing landfillis very far from the village Donowarih with a distance of approximately more dari15 miles by roadup kontour conditions down so it can be concluded is not likely to be transported to a landfill. Sothat the Village Donowarih require a landfill area (TPA) that is close and be able to serve the communityin the surrounding area.With topography at the foot of the mountain Arjuno the Landfill to be built so the potential topollute the environment, especially water and soil in areas that have a height below the surfaceDonowarih village, so it becomes very important that a comprehensive landfill design which focuseson health aspects of the environment.With reference to kaedah comprehensive planning Landfill is expected to have DonowarihVillage Landfill that meet environmental health standards are accompanied by a simple application ofwaste regulations for the village community Donowarih so it will get additional revenue through therecycling process that accumulates.